(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this paper is to identify the factors which are important for selection of any school at the time of admission. Moreover, the level of emotional intelligence among private and public school teachers has also been studied. This study is an empirical one. Descriptive research design has been used. Sample of 920 parents, 1030 students and 202 units of teachers have been used to collect data by using three structured questionnaires. Likert scale from “Not at all” to “To a great extent” has been an important module in the questionnaires. Collected data has been analyzed using descriptive statistics such as frequencies, percentages, cross tabulations. In addition to this chi square test and t-test have also been used with the help of SPSS. Significant difference has been observed among the parents selection of private or public school for their children. ‘Affordability’ and ‘Neighbourhood’ were ranked 1st by parents whose children are going to government schools, while ‘All Round Development’, ‘Emphasis on English Speaking’ and ‘Career Advantage’ are being ranked 1st by the parents whose children are going to private schools. Status of the school is also found an important factor in case of private schools. The study also reveals that private school teachers are little more emotionally intelligent than the public school teachers, which has a direct impact on their efficiency. This paper helps the school authorities in formulating the policies, rules and regulations in order to enhance the efficiency of public schools so that the parents may send their children to public schools without having a second thought.